2019
DOI: 10.1039/c8ta11407b
|View full text |Cite
|
Sign up to set email alerts
|

Selenium vacancy-rich CoSe2 ultrathin nanomeshes with abundant active sites for electrocatalytic oxygen evolution

Abstract: CoSe2 ultrathin nanomeshes with abundant selenium vacancies have been synthesized through a plasma-exfoliation method and exhibit an excellent OER performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
75
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(82 citation statements)
references
References 40 publications
2
75
0
Order By: Relevance
“…Zhang and co‐workers designed CoSe 2 ultrathin nanomesh materials with rich selenium vacancies (CoSe 2 UNMvac) via a plasma‐exfoliation treatment of layered hybrids (Figure 12f). [ 196 ] The prepared CoSe 2 UNMvac exhibited excellent electrocatalytic activities for OER with lower overpotential of 284 mV to deliver 10 mA cm −2 compared with the activities of CoSe 2 nanoparticles (466 mV@10 mA cm −2 ) and CoSe 2 nanosheets (343 mV@10 mA cm −2 ), indicating that the introduction of Se vacancy facilitated the enhancement of catalytic activity by favoring the transformation of surface CoSe 2 into highly active CoOOH.…”
Section: Electrochemical‐related Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang and co‐workers designed CoSe 2 ultrathin nanomesh materials with rich selenium vacancies (CoSe 2 UNMvac) via a plasma‐exfoliation treatment of layered hybrids (Figure 12f). [ 196 ] The prepared CoSe 2 UNMvac exhibited excellent electrocatalytic activities for OER with lower overpotential of 284 mV to deliver 10 mA cm −2 compared with the activities of CoSe 2 nanoparticles (466 mV@10 mA cm −2 ) and CoSe 2 nanosheets (343 mV@10 mA cm −2 ), indicating that the introduction of Se vacancy facilitated the enhancement of catalytic activity by favoring the transformation of surface CoSe 2 into highly active CoOOH.…”
Section: Electrochemical‐related Reactionsmentioning
confidence: 99%
“…In addition to CO, HCOOH is a valued liquid chemical for CO 2 RR, and can be used for hydrogen storage and transport. [ 106,196 ] Gong and co‐workers [ 197 ] found that moderate content of oxygen vacancies in SnO x results in a more active surface and can inhibit undesirable HER. Oxygen vacancy also could tune the bond strength between intermediates of HCOO* and SnO x , resulting in excellent electrocatalytic activity and selectivity for the production of HCOOH.…”
Section: Electrochemical‐related Reactionsmentioning
confidence: 99%
“…Analogously, ultrathin CoSe 2 nanomeshes (CoSe 2 UNM vac ) catalyst with abundant selenium vacancies was fabricated via plasma treatment. 52 The generation of selenium vacancies with the exposure of abundant catalytic active sites resulted in improved catalytic performance. Lately, Qiao and co-workers prepared highly efficient HER electrocatalysts with controllable phosphorus vacancies in nickel phosphides via readily thermal annealing using excessive sodium hypophosphite.…”
Section: Anion And/or Cation Vacanciesmentioning
confidence: 99%
“…Moreover, some other spectroscopic techniques, including electron paramagnetic resonance (EPR) and electron spin resonance (ESR) spectra, conduce to the analysis of the electronic environment around vacancies [38] . For example, CoSe 2 UNM vac shows an obvious EPR resonance and the calculated g value of 2.002, indicating the existence of Se vacancies (Figure 3c) [39] . And BiO 2‐x exhibits an obvious signal at the g value of 2.0 in the ESR spectrum, suggesting the presence of O vacancies in its structures (Figure 3d) [40]…”
Section: Introductionmentioning
confidence: 99%